Study of intra‐racial exclusion within Australian Indigenous communities using eco‐maps. (5th October 2016) - Doyle, Kerrie; Hungerford, Catherine; Cleary, Michelle
Abstract: In Australia, 'indigeneity' is not determined by skin colour, but rather by a person's heritage, acceptance by an indigenous community, and active participation in the affairs of that indigenous community. Some people who identify as indigenous, however, have experienced 'colourism' – that is, experiences of social exclusion because of the colour of their skin – from non‐Indigenous and also Indigenous Australians. This paper describes research that explored the effect of intra‐racial exclusion on the mental health and wellbeing of Indigenous Australians, with a particular focus on skin colour or 'manifest indigeneity'. Framed within a qualitative design, an eco‐map was used to guide in‐depth interviews with 32 participants that gave rise to personal stories that described the distress of experiencing intra‐racial colourism. Findings were derived from a thematic analysis that identified four major themes: 'Growing up black', 'Living on black country', 'Looking black', and 'Fitting in black'. These findings are important because they suggest a way forward for mental health nurses to better understand and support the mental health and wellbeing of Indigenous Australians who have experienced social exclusion as a result of colourism.